2011
DOI: 10.1177/1087054710389987
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Intimate Partner Violence Among Young Adult Males With Childhood ADHD

Abstract: Objective Research has clearly documented the social dysfunction of youth with attention-deficit hyperactivity disorder (ADHD). However, little is known about the interpersonal relationships of adults diagnosed with ADHD in childhood, including rates of intimate partner violence (IPV). Method Using data from the Pittsburgh ADHD Longitudinal Study, analyses compared the level of IPV (verbal aggression, violence) reported by young adult (18-25 year-old) males with childhood ADHD (n=125) to reports by demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
62
1
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 44 publications
10
62
1
1
Order By: Relevance
“…While preliminary, this is one of a small group of studies to find positive effects of treatment in a core domain of functional impairment for individuals with elevated ADHD symptoms (for others, see Barkley & Cox, 2007;Rostain & Ramsay, 2006;Weiss et al, 2012). Acknowledging the deleterious impact of ADHD symptoms on adult romantic relationships (e.g., Biederman et al, 2006;Canu, Tabor, Michael, Bazzini, & Elmore, 2014;Kessler et al, 2006;Wymbs et al, 2012), finding effects of the integrative group program on romantic relationships is encouraging. Improvement in relationship functioning may be valuable because it could facilitate romantic partners continuing to compensate for the difficulties of adults with elevated ADHD symptoms (Eakin et al, 2004).…”
Section: Discussionmentioning
confidence: 90%
“…While preliminary, this is one of a small group of studies to find positive effects of treatment in a core domain of functional impairment for individuals with elevated ADHD symptoms (for others, see Barkley & Cox, 2007;Rostain & Ramsay, 2006;Weiss et al, 2012). Acknowledging the deleterious impact of ADHD symptoms on adult romantic relationships (e.g., Biederman et al, 2006;Canu, Tabor, Michael, Bazzini, & Elmore, 2014;Kessler et al, 2006;Wymbs et al, 2012), finding effects of the integrative group program on romantic relationships is encouraging. Improvement in relationship functioning may be valuable because it could facilitate romantic partners continuing to compensate for the difficulties of adults with elevated ADHD symptoms (Eakin et al, 2004).…”
Section: Discussionmentioning
confidence: 90%
“…The case control studies of B. Wymbs et al (2012) and Mandell et al (1998) show a positive association for adult ADHD, unadjusted for childhood CD, or adult ASPD diagnosis. The study of B. T. Wymbs et al (2014) stresses the role of childhood ADHD as potentiating the association between problematic alcohol use and physical IPV.…”
Section: Evidence For the Association Between Adhd And Ipv/dvmentioning
confidence: 94%
“…Among a sample of young men ages 18 to 25 years, Wymbs et al (2012) found that ADHD diagnostic status in childhood (but not symptom severity) was associated with increased risk for violence toward romantic partners. Fang and colleagues (2010) found that retrospectively reported childhood symptoms of hyperactivity/impulsivity (HI) and inattention predicted IPV perpetration in a mixed-sex population-based sample (see also Theriault & Holmberg, 2001).…”
mentioning
confidence: 96%
“…A small body of research examining linkages between ADHD and IPV has focused exclusively on perpetration of IPV, particularly by men (Fang, Massetti, Ouyang, Grosse, & Mercy, 2010; Wymbs et al, 2012). Among a sample of young men ages 18 to 25 years, Wymbs et al (2012) found that ADHD diagnostic status in childhood (but not symptom severity) was associated with increased risk for violence toward romantic partners.…”
mentioning
confidence: 99%